Новеллы европейского патентного законодательства - Слобожанин, С.В. (Часопис Київського університету права, 2009)
Вступление в силу 1 мая 2008 г. Лондонского соглашения, а также принципиальные изменения патентных пошлин с 1 апреля 2009 г. с соответствующими изменениями Инструкций к ЕПК явились следующими значительными этапами в развитии европейского патентного законодательства. В статье освещаются наиболее важные для заявителя моменты, связанные с изменением законодательства, знание которых позволит заявителю проводить процедуру патентования в Европе наиболее рационально. Coming into effect of the London Agreement on the 1 May 2008, and also fundamental amendments of the fees since the 1 April 2009 with the corresponding amendments of the Regulations to the European Patent Convention became the next significant stages in the development of the European Patent Legislation. The most important for the applicant moments, related to the amendments of the legislation, knowledge of which will enable the applicant to carry out patenting procedure in Europe most efficiently will be covered in this article.